Comparison of the effects of rapid maxillary expansion versus Twin Block appliance on mandibular growth in skeletal Class II patients - Jia-Nan Zhang; Si Chen; Cheng-Yi Huang; Chong Zhong; Jing Jin; Feng-Yang Yu; Zan-Zan Zhang; Hai-Ping Lu (BMC, 2020)
Abstract Background This is a retrospective study that compares mandibular growth changes in skeletal Class II patients treated by rapid maxillary expansion (RME) and following fixed appliance with those patients treated by Twin-Block (TB) and following fixed appliance. Methods Fourteen patients treated by RME and following fixed appliance were included into the RME group. Fifteen patients treated by Twin-Block and following fixed appliance were included into the TB group. Lateral cephalometric radiographs taken before treatment and immediately after fixed appliance treatment were used to evaluate mandibular growth effects. Results The starting forms of the patients in the two groups were examined to be of good comparability. The mandibular length increased significantly in both groups as measured by Co-Gn, Go-Gn and Ar-Gn, but the TB group didn't show more mandibular growth than the RME group (P > 0.05). Skeletal changes of the mandible in vertical dimension were different in the two groups. The change in FMA was 0.35° in the RME group, while the change was 2.65° in the TB group (P < 0.001). The change in LAFH was 5.14 mm in the RME group, significantly smaller than the change of 10.19 mm in the TB group (P < 0.001). Conclusion The investigated Phase I treatment with RME followed by Phase II treatment of fixed appliance achieved the same increases in sagittal mandibular growth and facial profile improvements as the Twin-Block therapy. The treatment with RME followed by fixed appliance was better for vertical control, while the treatment with Twin-Block followed by fixed appliance significantly increased the mandibular plane angle.